The effects of compaction towards permeability of granular soils - Nur Aima Syafarina Binti Mohd Razi (School of Environmental Engineering, University Malaysia Perlis, 2014)
This paper summarizes and discusses the grain sizes of granular soil and the compactive effort that affect the dry density and permeability of granular soil. Several laboratory tests were carried out in order to ensure all the objectives in this project were successfully achieved. The tests involve are sieve analysis, compaction test and permeability test. This project focus more on determination of grain size distribution, the effects of compactive efforts which are varying number of blows and layers towards the dry density and permeability of granular soil and lastly the relationship between the dry density and permeability of granular soil.